2016
DOI: 10.1074/jbc.c116.744037
|View full text |Cite
|
Sign up to set email alerts
|

NHX-5, an Endosomal Na+/H+ Exchanger, Is Associated with Metformin Action

Abstract: Diabetes is one of the most impactful diseases worldwide. The most commonly prescribed anti-diabetic drug is metformin. In this study, we identified an endosomal Na ؉ /H ؉ exchanger (NHE) as a new potential target of metformin from an unbiased screen in Caenorhabditis elegans. The same NHE homolog also exists in flies, where it too mediates the effects of metformin. Our results suggest that endosomal NHEs could be a metformin target and provide an insight into a novel mechanism of action of metformin on regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…The level did not fully recover to that of the wild type that was not treated with metformin, but the difference between the mutant and the wild type was large and clear. The data support that the eNHE might be the site of action for metformin's function during starvation in C. elegans .…”
Section: Late Endosomes/lysosomes: the Hub Of Metabolism And The Misssupporting
confidence: 68%
See 2 more Smart Citations
“…The level did not fully recover to that of the wild type that was not treated with metformin, but the difference between the mutant and the wild type was large and clear. The data support that the eNHE might be the site of action for metformin's function during starvation in C. elegans .…”
Section: Late Endosomes/lysosomes: the Hub Of Metabolism And The Misssupporting
confidence: 68%
“…Metformin inhibition of mitochondrial complex I is conserved in Caenorhabditis elegans ; metformin delays development in well‐fed conditions and reduces life span during starvation . Kim et al found metformin reduces oxygen consumption in C. elegans .…”
Section: Metformin‐interacting Molecules: Metformin Transporters and mentioning
confidence: 99%
See 1 more Smart Citation
“…Since metformin has been reported to have some other targets ( Kim et al, 2016 ), we further used Compound C, a specific inhibitor of AMPK and another AMPK activator, AICAR, to examine whether metformin functioned via AMPK activation. Mice were divided into 5 groups ( n = 6–8 per group): normal, DSS with vehicle, DSS with metformin (500 mg/kg, p.o.…”
Section: Resultsmentioning
confidence: 99%
“…Increased Nhx1 expression in glucose-depleted cells might therefore help promote endocytosis and provide resources for survival during glucose starvation (65). Intriguingly, eNHE mutants in Caenorhabditis elegans (Nhx5) and fly (DmNHE3) were found to be resistant to metformin, a biguanide drug commonly used to treat type-2 diabetes, potentially through dysregulation of autophagy (66). Given that metformin is known to induce a caloric restriction-like state (67), our findings suggest that up-regulation of eNHE and alkalinization of endosomal pH may underlie response to metformin therapy.…”
Section: Nutrient Control Of Endolysosomal Phmentioning
confidence: 99%